Tinjauan Fondasi Bore Pile Pada Struktur Dinding Penahan Tanah Jalan Waipia-Saleman I Kabupaten Maluku Tengah - Renngur, Siti Hajar; Titaley, Henriette Dorothy; Abdin, Maslan (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Ambon, 2025)
The foundation is a lower structure that transfers the load from the upper structure to the ground below. On the Waipia - Saleman I road section on Central Maluku Regency at STA 35+000, 200 m long cantilever retaining wall was built and combined with 60 cm diameter bore pile foundation with a depth of 14 m which functions to secure slope areas that are prone to landslides This study aims to calculate the load received by the bore pile foundation, the bearing capacity and the settlement that occurs in the bore pile foundation. The bearing capacity of a single pile is calculated from N-SPT data using conventional methods, namely the Maverhoff method and the Reese & O'Neil methods. The bearing capacity of the pile group is calculated using the efficiency value from the Converse-Labarre Formula. The calculation of the settlement of a single pile and the settlement of the pile group are calculated based on the Vesic method. Based on the calculation results, the smallest load on the bore pile foundation was 1502.88 kN, with a distributed load at the base of the retaining wall of 41.75 kN/m2. The calculation resulted of the single pile bearing capacity using the Mayerhoff method yielded an average allowable bearing capacity (Qall) of 153 7.34 kN, and using the Reese & O’Neil method, the lowest permissible bearing capacity (Qall) at Bore Hole 02 was 1118.67 kN. The smallest group pile allowable bearing capacity (Qgall) at Bore Hole 02 was 2505.82 kN. The settlement calculation of the bore pile foundation using the Vesic method for single piles (S) was 0.0420 m, and for group piles (Sg) was 0.0939 m, which was considered safe and technically acceptable because it was smaller than the allowable settlement (Si), which was 0.151 m.Keywords: Bore Pile Foundation, Bearing Capacity, Settlement